2013
DOI: 10.3390/w5041517
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stakeholders’ Attitudes towards Water Markets in Southern Spain

Abstract: This research examines stakeholders' perceptions of and preferences for water markets in agriculture, focusing on the likely barriers that might refrain them from participating in such markets. The research was carried out on the Guadalquivir River Basin and involved semi-quantitative methods, combining a structured survey and focus group discussions. A very simple questionnaire was administered to each irrigation stakeholder (i.e., managers, water right holders and non-holders). The main result is that stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…In any case, because of the historical and traditional success of lobbying [53], water users belonging to these pressure groups may be less incentivized to participate in water markets, since they could expect to obtain new water rights for free as a consequence of this pressure from lobbyists. In any case, it is worth mentioning that Giannoccaro et al [42] did not find the same evidence in the Guadalquivir River Basin, since they found that potential buyers of water rights would not refrain from buying water to put pressure on obtaining new (free) water rights.…”
Section: Lobbying As a Nonmarket Way To Obtain Additional Water Resoumentioning
confidence: 83%
See 4 more Smart Citations
“…In any case, because of the historical and traditional success of lobbying [53], water users belonging to these pressure groups may be less incentivized to participate in water markets, since they could expect to obtain new water rights for free as a consequence of this pressure from lobbyists. In any case, it is worth mentioning that Giannoccaro et al [42] did not find the same evidence in the Guadalquivir River Basin, since they found that potential buyers of water rights would not refrain from buying water to put pressure on obtaining new (free) water rights.…”
Section: Lobbying As a Nonmarket Way To Obtain Additional Water Resoumentioning
confidence: 83%
“…In any case, there is little evidence about the attitudes and behavior of different stakeholders towards the potential revision of water concessions in Spain. This barrier has been only studied by Giannoccaro et al [42], who find that while more than a half of interviewed stakeholders in the Guadalquivir River Basin were worried that their water right could be questioned by water authorities, this concern could not be confirmed in the case of farmers.…”
Section: Administrative Authority To Grant or Revise Water Concessionsmentioning
confidence: 99%
See 3 more Smart Citations